Sanguisorba officinalis L. suppresses non-small cell lung cancer via downregulating the PI3K/AKT/mTOR signaling pathway based on network pharmacology and experimental investigation - Li, Hong; Lin, Jing; Yang, Fei; Deng, Junzhu; Lai, Jia; Zeng, Jing; Zou, Wenjun; Jiang, Nan; Huang, Qianqian; Li, Hua; Liu, Jian; Li, Mao; et al. (Frontiers in Pharmacology, 2022)
Background: Sanguisorba officinalis L. (SOL), a traditional Chinese herbal medicine called Diyu, has been shown to have potent antitumor effects. However, the role of SOL in suppressing non-small cell lung cancer (NSCLC) remains unknown. Purpose: This study was designed to investigate the pharmacological effects and mechanisms of SOL activity in NSCLC in vitro and in vivo. Methods: Network pharmacology was used to analyze the effects of SOL in NSCLC and its possible targets. Cell counting kit 8 (CCK8) and 5-Ethynyl-2-deoxyuridine (EdU) staining, western blot, flow cytometry of Annexin Ⅴ/propidium iodide (PI), and Hoechst 33342/PI staining were used to analyze the in vitro effects of SOL, while hematoxylin and eosin staining, immunohistochemistry, and western blot were used to examine in vivo outcomes. Results: Based on network pharmacology predictions, we analyzed 208 common targets between SOL and NSCLC, of which 36 core targets were obtained through Cytoscape analysis. The top 10 core targets included AKT, mammalian target of rapamycin (mTOR), and epidermal growth factor receptor. The Kyoto Encyclopedia of Genes and Genome analysis highlighted the phosphoinositide 3-kinase (PI3K)-Akt signaling pathway as the most likely relevant pathway. CCK8 and EdU assays identified anti-proliferative effects of SOL in A549 and H1299 cells. Immunohistochemical analysis of Ki67 expression revealed that SOL effectively inhibited tumor growth in vivo. SOL also considerably inhibited the migration and invasion of A549 and H1299 cells and markedly increased the percentage of PI-positive cells, while analysis of cell death in A549 cells indicated that SOL induced apoptosis. Poly (ADP-ribose) polymerase-1 (PARP-1) and caspase-3 were also found to be activated by SOL in A549 and H1299 cells in a dose-dependent manner. The in vivo results were consistent with those obtained in vitro. Conclusion: SOL treats NSCLC by inhibiting the PI3K/Akt/mTOR pathway and simultaneous activation of caspase-3, leading to cleavage of PARP-1 to promote apoptosis of cancer cells. These results highlight the possibility of SOL to serve as a future novel therapeutic agent for NSCLC.